“Internal carotid artery-type cervical spondylosis” is not supported as an independent subtype: a perspective on diagnostic classification and clinical differentiation - Tianjun Zhai; Yeping Chen; Wei Feng; Hui Zhang (Frontiers in Neurology, 2026)
Cervical spondylosis is a common degenerative disorder, yet its diagnostic boundaries may be inappropriately expanded when nonspecific symptoms such as dizziness coexist with age-related cervical imaging changes. This Perspective evaluates the hypothetical concept of “internal carotid artery-type cervical spondylosis” and whether it qualifies as an independent clinical subtype. Using an adapted validity–utility framework, the proposed entity was assessed according to five criteria: a specific anatomical relationship, a reproducible pathophysiological mechanism, a recognizable clinical phenotype, supportive imaging or ancillary evidence, and independent diagnostic utility. Unlike the vertebral artery, the cervical internal carotid artery has no consistent anatomical relationship with routine degenerative cervical structures. Rare bony–carotid conflicts may occur, but these are anomaly-driven vascular lesions and do not establish a general degenerative subtype. Nonspecific dizziness does not localize pathology to the internal carotid artery, whereas focal anterior-circulation symptoms are better explained by established carotid or cerebrovascular disorders. Clinically, transient monocular visual loss, aphasia, hemiparesis, focal cortical deficits, or new unilateral head or neck pain with partial Horner syndrome or cranial nerve findings should prompt urgent vascular or stroke-oriented evaluation. Current evidence therefore does not support “internal carotid artery-type cervical spondylosis” as an independent subtype. Maintaining clear diagnostic boundaries may reduce mislabeling and improve patient safety.